Scintillation detectors for the TAIGA experiment - Astapov, I.; Bezyazeekov, P.; Gorbunov, N.; Grebenyuk, V.; Gress, O.; Gress, T.; Grishin, O.; Grinyuk, A.; Horns, D.; Ivanova, A.; Kalmykov, N.; Kazarina, Y.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
It is planned that new TAIGA-Muon detectors will complement the existing Tunka-GRANDE facility of scintillation detectors of the TAIGA gamma-observatory in the Tunka valley, Russia. The new design of scintillation detector with wavelength shifting bars and PMTs is developed. The first prototype of the counter was installed and tested using infrastructure of the Tunka-GRANDE installation in 2017. The mass production of counters has begun in 2018 at the Novosibirsk State University.